Filosofi Mangalap Tondi Pada Budaya Batak Toba dalam Kaitannya dengan Model Antropologis Stephen Bevans - Blareq, Yoseph Koverino Gedu; Purba, Merry Johanna (Perspektif, 2024)
This paper is entitled the philosophy of mangalap tondi in Toba Batak culture in relation to Stephen Bevan's anthropological model.  Mangalap tondi is a form of ceremony to pick up the spirit of someone who has left due to an accident or illness. Bevans' anthropological model has a connection with mangalap tondi which talks about the spirit that gives salvation and strength. The purpose of this paper is to discuss how and the symbols needed in the mangalap tondi ritual. The method used in this paper is a qualitative description method with a literature review approach, which is a study conducted to analyze literature from various sources so that it becomes a conclusion and a new idea. The author also uses the interview method to strengthen the basis of previous journal writings.